Determinants of entrepreneurial behaviour among orang asli in peninsular malaysia : an extended theory of planned behaviour framework - Nor Emmy Shuhada, Derani (2024)
Poverty is a worldwide problem which crucially impacted on marginalized communities such as the Orang Asli people. Entrepreneurship is considered as a means of escaping the woes of poverty and improving the livelihood of the community. Hence, indigenous entrepreneurship has also been given the nudge through various government programmes to decrease incidence poverty among the Orang Asli. Hence, it is necessary to understand their entrepreneurial behaviour so that the right intervention could effectively contribute towards decreased rate of poverty. This study used an enriched Theory of Planned Behaviour with the addition of self-reliance and self-sufficiency from the Self-Identity Theory to examine the determinants of entrepreneurial behaviour among Orang Asli. Based on a post-positivist paradigm, this cross-sectional and quantitative study gathered information using survey questionnaire from the population of Orang Asli entrepreneurs. Using 216 valid datasets, this study employed a PLS-SEM approach to analyze data and generate the empirical findings. A total of 12 research hypotheses were tested whereby six were supported. Findings showed that attitude, subjective norms and self-reliance positively and significantly influence entrepreneurial intention but not self-sufficiency. Self-reliance significantly predicts self-sufficiency and actual behavioural control significantly predicts perceived behavioural control. Besides that, the moderating effect of perceived behavioural control on the relationships of attitude and subjective norms with entrepreneurial intention were not significant. Likewise, the moderating effects of perceived and actual behavioural control on the relationship between entrepreneurial intention and entrepreneurial behaviour were not significant. Self-sufficiency also did not mediate the relationship of self-reliance with entrepreneurial intention. The effect of entrepreneurial intention on entrepreneurship behaviour was positive and significant. The model showed substantial predictive accuracy with R2 of 0.553 to explain entrepreneurial intention and an R2 of 0.640 to explain entrepreneurial behaviour and PLSpredict indicated that the model has moderate predictive power. Findings implied the need for the government to plan and implement entrepreneurial programs that are based on the essence of self-reliance and subjective norms while at the same time, promoting positive attitude towards entrepreneurship among the Orang Asli community.